2017
DOI: 10.1186/s12864-016-3472-x
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular proteome of two Bifidobacterium species reveals different adaptation strategies to low iron conditions

Abstract: BackgroundBifidobacteria are among the first anaerobic bacteria colonizing the gut. Bifidobacteria require iron for growth and their iron-sequestration mechanisms are important for their fitness and possibly inhibit enteropathogens. Here we used combined genomic and proteomic analyses to characterize adaptations to low iron conditions of B. kashiwanohense PV20-2 and B. pseudolongum PV8-2, 2 strains isolated from the feces of iron-deficient African infants and selected for their high iron-sequestering ability.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Non-closed pan-genomes are typical for heterogeneous datasets, like the Lactobacillus dataset in this study, for species with diverse habitats, like L. plantarum in this study , and in species with high acquisition of genes, such as natural competent streptococci [ 16 , 21 ]. Acquisition of genes occurs in lactobacilli occurs via HGT, which parallels observations in another genus frequently associated with the human gut: Bifidobacteria [ 43 ].…”
Section: Discussionmentioning
confidence: 69%
“…Non-closed pan-genomes are typical for heterogeneous datasets, like the Lactobacillus dataset in this study, for species with diverse habitats, like L. plantarum in this study , and in species with high acquisition of genes, such as natural competent streptococci [ 16 , 21 ]. Acquisition of genes occurs in lactobacilli occurs via HGT, which parallels observations in another genus frequently associated with the human gut: Bifidobacteria [ 43 ].…”
Section: Discussionmentioning
confidence: 69%
“…The other gene of the operon (LMG13195_RS01880) was also upregulated in coculture and encodes a protein annotated as an amino acid ABC transporter substrate-binding protein with a domain related to iron transport (Fe 2ϩ transport protein). Iron permease genes have been detected in B. breve and Bifidobacterium pseudolongum, as well as in B. bifidum strains, and their expression is increased in iron-limited conditions (31)(32)(33). Several genes involved in nucleotide transport and metabolism were downregulated in coculture ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study carried out by Vazquez-Gutierrez et al identified a number of iron uptake clusters utilising a proteomic approach, this analysis identified three ferrous iron transporters in the secretome of B. kashiwanohense PV20-2: AH68_00590 and AH68_00595 which are homologous to bfeUO , respectively, AH68_00600 which is homologous to sifA (Vazquez-Gutierrez et al, 2017 ). The presence of BfeUO and SifA homologs in these three bifidobacterial strains illustrate the importance of these two iron uptake system in sequestering this vital micronutrient.…”
Section: Discussionmentioning
confidence: 99%